2020
DOI: 10.2174/1389557519666191125121407
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides: Vestiges of Past or Modern Therapeutics?

Abstract: The ubiquitous occurrence of Antimicrobial Peptides (AMPs) in all domains of life emphasizes their crucial role as ancient mediators of host defense. Despite their antiquity and prolonged history of exposure to pathogens, endogenous AMPs continue to serve as effective antibiotics. An "evolutionary arms race" between host and pathogen resulted in structural diversity of AMPs, leading these molecules to retain activity against a wide range of pathogens, including antibiotic-resistant microbes. As the menace of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…AMPs are reported to destroy bacterial cells by permeabilizing the membrane, followed by depolarization (Mitra et al 2020 ; Bhatt Mitra et al 2020 ). To explore if UBI-APBA utilized this strategy to adversely affect the survival of S. aureus , depolarization and permeabilization of S. aureus membrane was studied by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPs are reported to destroy bacterial cells by permeabilizing the membrane, followed by depolarization (Mitra et al 2020 ; Bhatt Mitra et al 2020 ). To explore if UBI-APBA utilized this strategy to adversely affect the survival of S. aureus , depolarization and permeabilization of S. aureus membrane was studied by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…4 ). Several AMPs that demonstrate strong antibacterial activity encounter challenges due to their toxicity to human red blood cells (RBCs), leading to a diminished therapeutic potential (Mitra et al 2020 ). The low therapeutic index or TI (TI = Haemolytic dose /MIC causing 50% lysis or HD 50 ) of such AMPs make their clinical translation extremely difficult.…”
Section: Resultsmentioning
confidence: 99%
“…When the effects of bacteriocin-producing L. plantarum on the intestinal immunological barrier were explored, the results revealed that the two strains promoted the release of IgA and IgG in the serum and intestine to varying degrees, which suggested that bacteriocin-producing strains could strengthen the intestinal immune function, but there existed differences when different strains acted on immunoglobulins in distinct tissues of mice. Antimicrobial peptides are crucial participants in host natural defense and play a significant part in innate immunity [ 25 ]. The antimicrobial peptide RegIIIγ, produced by Paneth cells, can protect mice from pathogens infection, regulate intestinal microecological balance, and maintain immune homeostasis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMPs represent an attractive class of molecules for antimicrobial drug development due to their intrinsic wide-spectrum antimicrobial activity. Several efforts have been undertaken to move AMPs into the clinic as effective therapeutics with little success due to the toxicity issues associated with this class of molecules and their high manufacturing costs( 21 ). To overcome these obstacles, recent efforts focused on alleviating these issues by designing USAMPs that can be attractive candidates for drug development as they would allow large-scale production with economic feasibility and provides a significant reduction in manufacturing costs due to simplicity in their structure and short amino acid sequence.…”
Section: Discussionmentioning
confidence: 99%